...Mas a gente não sabe que roupa dever usar : um estudo sobre a prática do psicólogo no Centro de Referência de Assistência Social - Araujo, Fabiana Itaci Corrêa de (2010)
The present research aims to analyze the pratical of psychologists of Social Assistance Centers (CRAS) in its implication with the subjectivity as a dimension of action in the Social Security Politics. The qualitative study was developed from the perspective of the Critical Social Psychology Theory, with a historical dialectical materialist basis. In order to accomplish our objective, three psychologists had been interviewed (half-directed interview). They worked at the public, municipal service, servers of the CRAS for, at least, six months. From the stories produced with the interviews, units of sense had been raised. Hence, those units were collated having as reference the norms of Social Security and the principles of Critical Social Psychology. This was done in dialog with others researches of NEXIN that were about similar themes. In this process it is evident the importance attributed to the practical knowledge developed by the Social Service, the daily attendance to the demands of the population, the importance of the group as privileged unit of work and the purpose attributed for the psychologist for its practical professional in this social-occupational space. The results point the character of process in the construction of a proper place of Psychology in the Social Assistance, and demonstrate the political difficulties joined during the formation and organization of the work of accomplishing the objectives of the basic social protection. This construction is crossed by the contradictions that determine the Social Assistance as an area of public politic, understood in the movement of the production and reproduction of the social life, and of the historical constitution of Psychology as an area of knowledge and practical professional